Relationships among Idiosyncratic Uncertainty, Managerial Flexibility and Capital Investment within the Companies Listed in Tehran Stock Exchange (Shahid Bahonar University of Kerman, 2013)
This research investigates the relationships among future uncertainty (for real options) and managerial flexibility and capital investment. For measuring managerial flexibility two criteria of firm size and financial constraint are used, and for measuring future uncertainty the criterion of stock return. Statistical sample consists of 107 manufacturing firms listed in Tehran Stock Exchange, and time period of research is 2002 to 2010. In this research, the estimating model is explained by multivariable regression to test the hypothesis, using panel data model. The findings show that there is a significant positive relationship between future uncertainty and capital investment. Also,  there is a significant positive relationship between future uncertainty and financial constraint with capital investment. At least a significant negative relationship between future uncertainty and firm size with capital investment has been found.